Finite-time stability of a class of nonlinear fractional-order system with the discrete time delay - Wang, F.; Chen, Diyi; Zhang, Xinguang; Wu, Yong Hong (Taylor and Francis, 2017)
© 2016 Informa UK Limited, trading as Taylor & Francis Group.This paper investigates the finite-time stability problem of a class of nonlinear fractional-order system with the discrete time delay. Employing the Laplace transform, the Mittag-Leffler function and the generalised Gronwall inequality, the new criterions are derived to guarantee the finite-time stability of the system with the fractional-order 0 < a < 1. Further, we propose the sufficient conditions for ensuring the finite-time stability of the system with the fractional-order 1 < a < 2. Finally, based on the modified Adams–Bashforth–Moulton algorithm for solving fractional-order differential equations with the time delay, we carry out the numerical simulations to demonstrate the effectiveness of the proposed results, and calculate the estimated time of the finite-time stability.